2005
DOI: 10.1109/tap.2004.842681
|View full text |Cite
|
Sign up to set email alerts
|

Compact slot and dielectric resonator antenna with dual-resonance, broadband characteristics

Abstract: Abstract-The goal of this study is to improve the bandwidth of a miniaturized antenna. The proposed technique combines a slot antenna and a dielectric resonator antenna (DRA) to effectively double the available bandwidth without compromising miniaturization or efficiency. With proper design it is observed that the resonance of the slot and that of the dielectric structure itself may be merged to achieve extremely wide bandwidth over which the antenna polarization and radiation pattern are preserved. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
96
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(100 citation statements)
references
References 22 publications
(26 reference statements)
0
96
0
Order By: Relevance
“…The resonant frequencies of DRA are not equal to that of the DR and cross-slot because the microstrip feed line has effects on the position of the resonances of the DRA [10]. This provides evidence that the proposed antenna is a dual-band hybrid DRA.…”
Section: Parameter Analysis and Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The resonant frequencies of DRA are not equal to that of the DR and cross-slot because the microstrip feed line has effects on the position of the resonances of the DRA [10]. This provides evidence that the proposed antenna is a dual-band hybrid DRA.…”
Section: Parameter Analysis and Discussionmentioning
confidence: 94%
“…With the development of wireless communication systems, DRAs with dual-band performance have been widely investigated [3][4][5]. Hybrid DRA [6][7][8][9][10][11][12] technology is a viable candidate for realizing dual-band operation. A direct approach to designing a hybrid DRA is to introduce an extra slot resonator [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A dual-band antenna is a key component for such communication systems [3][4][5][6][7][8][9], especially for "universal" applications, where it should be covering the whole 2.4-2.484 GHz and 5.15-5.825 GHz bands for dual-band WLAN. Designs range from those based on branched monopole [3,4], dipole [5,6], or multibranch [7,8] to those based on dielectric resonators. Recently, it has been demonstrated that loading with magnetic resonator can facilitate dual-band operation [9].…”
Section: Introductionmentioning
confidence: 99%